Analisis Perubahan Garis Pantai Menggunakan Digital Shoreline Analysis System: Studi Kasus Wilayah Pesisir Kota Jayapura, Provinsi Papua - Baigo Hamuna; John Dominggus Kalor (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2022)
Study of shoreline change is an important step in understanding the dynamics in the coastal area in Jayapura City and is a first step to reduce the risk of coastal erosion and also minimize social, physical and economic losses. This research was conducted in the coastal area of Yos Sudarso Bay, Jayapura City, Papua Province by utilizing multi-temporal Landsat satellite imagery (Landsat 5 TM, Landsat 7 ETM+ and Landsat 8 OLI-TIRS) for 1994, 2000, 2007, 2014 and 2020. Analysis Shoreline changes are determined using the Digital Shoreline Analysis System (DSAS). End Point Rate (EPR), Net Shoreline Movement (NSM) and Linear Regression Rate (LRR) are used to calculate the rate of change of the coastline and predictions of change of the coastline for the next 10 years. The results showed that in the period 1994-2000 there was an area of 535749.22 m2 of abrasion and 399361.87 m2 of accretion. During the 2000-2007 period, 453,876.10 m2 of abrasion occurred and 447,121.39 m2 of accretion. In the 2007-2014 period there was 781,274.83 m2 of abrasion and 259,221.26 m2 of accretion. In the 20014-2020 period, 93,328.79 m2 of abrasion occurred and 74,204.42 m2 of accretion. Spatially, the coastal areas of Yos Sudarso Bay, Jayapura City, which experienced abrasion included Holtekamp Beach, Hamadi Beach, and a small part in Youtefa Bay, while those that experienced accretion included DOK II Beach, Entrop Beach, Ciberi Beach, in Youtefa Bay and Cape Ria. The shoreline changes rate (LRR) in the coastal area of Yos Sudarso Bay, Jayapura City due to abrasion in the period 1994 to 2020 is 0.89 m/year, while the shoreline change rate due to accretion is 0.70 m/year. Based on the prediction of shoreline changes at Holtekamp Beach, it is predicted that the highest abrasion will occur as far as 50.19 m with an average abrasion distance of 20.22 m, while the highest accretion is as far as 19.19 m with an average accretion distance of 10.55 m.